A Schematic Framework for the Construction of an Ethnorelativism-Based Social Harmony Model in the Local Wisdom of Memarek - I Wayan Ardhi Wirawan; Pawan Kumar; I Wayan Sutama; I Putu Sarjana; Ni Luh Gede Hadriani (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relations, 2026)
This article presents the findings of a study aimed at identifying the systematic process of constructing a social harmony model based on ethnorelativism within the local wisdom of memarek, involving the Sasak-Muslim and Balinese-Hindu communities in Selelos Village. The study employed a qualitative approach using a descriptive-interpretative method based on interview, observation, and documentation data. The findings reveal that the initial historical encounter between the two communities was characterized by social distance due to ethnic and religious differences, as well as the absence of mutual trust. However, the Balinese community's agricultural expertise became the entry point for the diffusion of innovation, facilitating knowledge exchange, cooperation, and intensive communication. This process followed the stages of innovation, communication, adoption, and confirmation, as described in Everett M. Rogers' Diffusion of Innovations Theory. The study also demonstrates that sustained contact, shared goals, cooperation, and institutional support strengthened interethnic relations, consistent with Gordon W. Allport's Contact Theory. Furthermore, agricultural skills evolved from cultural capital into social capital, reinforcing networks of trust and solidarity between the two communities. Continuous interaction transformed the communities' orientation from ethnocentrism to ethnorelativism, leading to social integration characterized by mutual respect, participation in customary traditions, and the establishment of sustainable social harmony in Selelos Village.